Urgensitas Kompetensi Literasi Digital Pustakawan Sebagai Aktor Komunikasi Ilmiah dalam Menunjang Transformasi Digital - Mukhlis (Pustabiblia: Journal of Library and Information Science, 2025)
Digital transformation in librarianship, particularly for librarians as actors in scholarly communication, marks a new era in the governance of digital knowledge products. This transformation presents opportunities for libraries to enhance their operational efficiency through technological integration. In this context, librarians’ digital literacy is a critical competency that supports the success of digital transformation in libraries. This competency extends beyond technological proficiency to include skills in managing and disseminating knowledge products, encompassing cultural heritage, local wisdom, and general knowledge. This study aims to explore the readiness of libraries in facing digital transformation, particularly in ensuring the sustainable accessibility of cultural heritage through digitization. The research employs a qualitative descriptive approach with an interpretative and constructivist perspective. Data collection is conducted through a literature review, while data analysis follows the Miles & Huberman model, comprising data reduction, data display, and verification. The findings indicate that the success of library digital transformation depends on three key aspects: operational agility, customer-centricity, and workforce competencies. Librarians’ digital literacy is a crucial factor in navigating these changes, encompassing technological capabilities, media interpretation, and skills in access, management, innovation, and collaboration. Furthermore, the digitization of cultural heritage has been identified as a priority to ensure broader access to information and the sustainable preservation of cultural assets in a modern format. Thus, librarians’ digital literacy is a determining factor in maintaining the relevance of libraries in the digital era and meeting the evolving information needs of society.